Nasihat Al-Mulk: Pemikiran Politik Raja Ali Haji Perspektif Etik - Alimuddin Hassan Palawa (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
The image of a good ruler is always to meet the needs of his people and think about the life (fate) of his people. With this kind of leadership behavior, the people will be prosperous and peaceful and people always obey it because in the hearts of the people terpatri fame the wisdom of its leader leaders. In addition, a good ruler is not indulging his lust, avoiding disgraceful nature and attitude and avoiding unfavorable world life. Furthermore, Raja Ali Haji mentioned that the good ruler will build facilities and infrastructure in support of the achievement of the welfare of the community, reducing the occurrence of slander in society, religion maintained and custom preserved, education is noticed, law is enforced and the community is finally close to God. In the section of Raja Ali Haji detailing the characteristics of a ruling ruler, which reigns with